THE USE OF GRAPHIC CALCULATOR IN MATHEMATICS LEARNING: IS IT STILL RELEVANT? - Dirgantoro, Kurnia Putri Sepdikasari (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
In the middle of the advancement of technology today where the rapid development of a wide range of software that can be used in mathematics, it seems the use of graphing calculators in the classroom are being abandoned. Relatively expensive, parents and schools tend to think twice before buying a graphing calculator for their children as well as the availability of media learning in school. However, is it true that the used of graphic calculator are not relevant at this time? It is intended to be a review of theory to answer these questions.